Povezanost kvalitete života i psihološkog aspekta bolesnika s acne vulgaris - Kotrulja, Lena (Array, 2003)
Acne vulgaris is a common inflammatory dermatosis that can produce psychological and physical scarring. It is common for the patient to develop psychological problems as a consequence of the condition, such as those related to low self-esteem, social phobias, depression, anxiety, suicidal thoughts, and lowered quality of life. Self-assessment af acne severity is often more severe than clinical dermatological evaluation, which is important for understanding the necessity of individual approach to the patient. Isotretinon is indicated in the treatment of severe form of the disease, although its application has also been suggested lately in moderate form of acne with prominent cicatricial liability or when the disease has a strong psychological impact on patient's life. In the last 15 years, there has been evidence of possible association of isotretinoin therapy with depression and suicidal tendency during treatment. The aim of our clinical trial, conducted at two Dermatological Departments in Croatia, was to determine how patients with acne vulgaris cope with their disease and what is the influence of isotretinoin therapy on psychological status of the patient. Acne severity was determined by a dermatologist using validation grading system. Patients were asked to self-rate their condition. Quality of life was measured by DSQL ; subjects also completed APSEA, BDI, STAI and MPS Inventory. The results showed that patients with acne suffered from psychosocial problems induced by their disease. The disability associated with acne correlated inconsistently with clinical grading of acne severity, but showed a good correlation with self-rated severity of the condition. It seems that the impairment caused by acne does not correlate with the objective clinical assessment of acne severity. The most important factor is the patient's perception of their condition. Therefore, it is important for the future research to indlude severity ratings by both the patients and dermatologists.